The Metabolic Response to Postnatal Leptin in Rats Varies with Age and may be Litter Dependent - Granado, M.; Diaz, F.; Fuente-Martín, E.; García-Cáceres, C.; Argente, J.; Chowen, J. A. (Hormone and Metabolic Research, 2014)
Hyperleptinemia during postnatal life induces long-term effects on metabolism. However, these effects are controversial as both increased and decreased propensity towards obesity has been reported. To further analyze the effects of chronic neonatal hyperleptinemia on the subsequent metabolic profile, male Wistar rats proceeding from 18 different litters (8 pups/litter) received a daily subcutaneous injection of either saline (10 ml/kg, n=36) or leptin (3 μg/g, n=36) from postnatal day (PND) 2 to PND9. Rats were sacrificed at 10, 40, or 150 days of age. At 10 days of age, leptin treated rats had decreased body weight (p<0.001) and body fat (p<0.05). Leptin levels and glycemia were increased (p<0.01), whereas insulin, total lipids, triglycerides and glycerol levels were decreased (p<0.05). At PND40 rats receiving leptin had increased glycemia (p<0.01) and plasma HDL and LDL levels, but decreased total lipids (p<0.05). At PND150 neonatal leptin treatment induced different effects in rats raised in different litters. Rats from litter 1 had increased body weight (p<0.05), body fat (p<0.01), and plasma leptin (p<0.001), cholesterol (p<0.001), triglyceride (p<0.001), total lipid (p<0.001), LDL (p<0.05), and glycerol (p<0.001) levels. In rats from litter 2 these parameters did not differ from controls. Rats from litter 3 had decreased body weight (p<0.05), visceral fat (p<0.01) and plasma leptin (p<0.001), cholesterol (p<0.001), triglyceride (p<0.001), glycerol (p<0.001), and HDL (p<0.001) levels. In conclusion, the metabolic response to postnatal leptin varies with age, with the response in adulthood being variable and most likely influenced by other factors, including the genetic make-up.
Keywords: postnatal leptin; metabolic programming; hypothalamus